A rare case of gradual enlargement of a multifocal myelolipoma of the posterior mediastinum for 12 years after surgical resection of an adrenal myelolipoma. (2018) - Haro, Akira; Fujishita, Takatoshi; Nishikawa, Haruka; Taguchi, Yoshihiro; Kouda, Takuyuki; Kajiwara, Koutaro; Makino, Hideki; Kanematsu, Takanori; Oshiro, Yumi; Yokoyama, Hideki
Highlights: A myelolipoma is a rare benign tumor comprising adipose tissue and normal hematopoietic cells. A myelolipoma commonly occurs in the unilateral adrenal gland. This is the first rare case of multifocal myelolipomas of the mediastinum and adrenal gland. Abstract: Introduction: A myelolipoma is a rare benign tumor that is composed of adipose tissue and hematopoietic elements. Myelolipomas most commonly occur in the unilateral adrenal gland. Posterior mediastinal myelolipomas are extremely rare. We herein present a rare case of a multifocal myelolipoma of the mediastinum that gradually enlarged over a 12-year period after surgical resection of an adrenal myelolipoma. This is the first report of multifocal myelolipomas of the posterior mediastinum and adrenal gland. Presentation of case: A posterior mediastinal tumor was incidentally found by chest X-ray and computed tomography (CT) examination of a 74-year-old woman. The patient had a medical history of resection of a myelolipoma of the left adrenal gland 12 years earlier. We performed tumor extirpation under video-assisted thoracic surgery (VATS). The size of the tumor was 4.5 cm, and the postoperative diagnosis was a myelolipoma. Discussion: Posterior mediastinal myelolipomas are extremely rare, and only 39 cases of mediastinal myelolipoma have been reported to date. No reports have described a multifocal myelipoma of mediastinal myelolipoma. To our knowledge, this is the first report of multifocal myelipomas of the adrenal gland and posterior mediastinum. Conclusion: A differential diagnosis of myelolipoma of the posterior mediastinum is important in patients with a history of myelolipoma of the adrenal gland.